2017
DOI: 10.21608/ejh.2017.3700
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Study of Titanium Dioxide Nanoparticle Effect on the Rat Renal Cortex and the Possible Protective Role of Lycopene

Abstract: Introduction: Titanium dioxide nanoparticles (TNPs) have a wide range of applications in industry, medicine and environmental technology. Nowadays, TNPs have raised researcher's concerns on their toxicity. Lycopene is a dietary carotenoid having a potent antioxidant effect. Aim: To evaluate the effect of TNPs on the structure of renal cortex of rats and to assess the possible protective effect of lycopene against TNPs nephrotoxicity. Material and methods: Forty five adult male rats were divided into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…As regards Masson's trichrome, staining sections from control group revealed normally distributed collagen fibers in the capsule and around blood vessels, results that were in agreement with those described by Abd Ellatief et al 2015; but in treated group revealed marked increase of collagen fibers especially in the capsule and around blood vessels; this result is in accordance with Salem et al (2017) and Altindag et al (2007) who proposed that the increased collagen fibers are due to the decrease in collagen metabolism that may be related with oxidative stress. In protective group, there was normal distribution of collagen fibers especially in testicular capsule and around blood vessels, a result that is in agreement with Gopal et al (2015).…”
Section: Discussionsupporting
confidence: 90%
“…As regards Masson's trichrome, staining sections from control group revealed normally distributed collagen fibers in the capsule and around blood vessels, results that were in agreement with those described by Abd Ellatief et al 2015; but in treated group revealed marked increase of collagen fibers especially in the capsule and around blood vessels; this result is in accordance with Salem et al (2017) and Altindag et al (2007) who proposed that the increased collagen fibers are due to the decrease in collagen metabolism that may be related with oxidative stress. In protective group, there was normal distribution of collagen fibers especially in testicular capsule and around blood vessels, a result that is in agreement with Gopal et al (2015).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding renal tubules, some were degenerated with numerous tubular dilation and most of their lumens contained homogenous acidophilic cellular debris. Some tubular cells appeared with dark stained pyknotic nuclei while others showed cytoplasmic degeneration or vacuolations in consistent with Altayeb et al, (2017) [38] who revealed changes as; flattening of the epithelial lining of some tubules, exfoliation and pyknosis of some tubular cells with apparent luminal dilatation and intratubular cell debris.…”
Section: Discussionsupporting
confidence: 88%
“…Fartkhooni et al, (2016) [37] in their study also reported swelling and dilatation of Bowman's capsule. Also, Altayeb et al, (2017) [38] documented several renal histopathological changes associated with dilated congested glomerular capillaries. Regarding renal tubules, some were degenerated with numerous tubular dilation and most of their lumens contained homogenous acidophilic cellular debris.…”
Section: Discussionmentioning
confidence: 97%
“…Fibroblasts increase their numbers and secrete huge amounts of extracellular matrix. Finally, prolonged injury to the renal parenchyma and renal failure take place [12,42].…”
Section: Discussionmentioning
confidence: 99%